Genetic diversity and population structure of sweetpotato accessions (Ipomoea batatas [L.] Lam.) revealed by single nucleotide polymorphism markers - Nomusa Chizhande; Sibiya, Julia; Gasura, Edmore; Mutari, Bruce; Chaingeni, Davison; Dumisani Kutywayo; Musundire, Lennin; Mathew, Isack; Emeline Dossa (Wiley, 2025)
Use of molecular markers has improved the analysis of genetic variation by eliminating environmental influences on genotype performance. The objective of this study was to assess the genetic diversity (GD) and population structure of 327 sweetpotato genotypes sourced from the major sweetpotato-growing regions of Zimbabwe and from the International Potato Centre (CIP) in Mozambique using low-density Diversity Array Technology (DArTseq) SNP chip covering the 90 chromosomes of sweetpotato. The genotypes' GD varied from 0.12 to 0.50, with a mean of 0.36. The mean PIC value of the SNP markers was 0.29. As SNP markers are biallelic with a maximum PIC of 0.50, this value indicates a moderate level of polymorphism. There was a good representation of minor alleles within the population, with an average minor allele frequency (MAF) of 0.26. The average observed heterozygosity of 0.12 was consistent with the cross-pollinating system in sweetpotato but could perpetuate a narrow genetic base. There was limited interbreeding between the populations of sweetpotato, as indicated by a mean fixation index (F) of 0.68. The high F values indicated that most alleles per genotype were contributed by one parent, which is unusual in allogamous species such as sweetpotato. The sweetpotato genotypes in this study could be clustered into two sub-populations with significant differences within the sub-populations. Genetic variation among genotypes is essential for the improvement of sweetpotato. Still, significant genetic gain could be achieved by cross-pollinating divergent genotypes with high MAF to create segregants with rare alleles. It is, thus, important to capture the rare alleles as they help adapt to current and future environmental shifts.